Lost - Staake, Bob, 1957- (asb, Anne Schwartz Books, 2024)
"Where, oh where is Kitty? She's not upstairs... not in her litter box... not at her food bowl. Hmm...There's only one thing to do: find this lost cat. As the cat's owner roams town in hopes of finding her pet, she discovers she's not the only one missing their beloved animal. There's also a lost dog...a lost bird...even a lost giraffe! Join the search party in this almost wordless story that celebrates helping our neighbors and gently reminds us that what is lost can always be found." --